Exploring the school climate in the formation of student-athlete morals at a sports school in Johor - Rahman, Siti Hajar; Che Hassan, Norlizah; Mohd Fakhruddin, Fathiyah; Salim, Siti Suria (Human Resource Management Academic Research Society, 2022)
Moral depravity is prevalent among adolescents nowadays, and student-athletes are not exempt from being exposed to bullying, electronic cigarette addiction, and other misconducts involving other adolescents. The school's climate is one of the social learning aspects that might contribute to students' well-being. Therefore, this study was conducted to explore the school climate as a determinant of social learning by focusing on the daily routines of students at the Johor State Sports School. Case study qualitative research approaches were utilized for this study and involved ten informants, including student-athletes, teachers, and principals. Data was gathered through in-depth semi-structured interviews, supplemented by participant observations, document analysis, and field notes. According to the study's findings, several aspects of empowering everyday activities, such as spiritual practises, physical health, academic balance, sports, morals, and student self-management, are present in the school environment. The findings of this study are expected to provide guidance and encouragement to the school, administrators, teachers, and the Malaysian Ministry of Education, particularly in maintaining a conducive and suitable school environment.